2006
DOI: 10.1002/hep.21003
|View full text |Cite
|
Sign up to set email alerts
|

TNF‐α–secreting monocytes are recruited into the brain of cholestatic mice†‡

Abstract: Signaling occurs between the liver and brain in cholestatic liver disease, giving rise to sickness behaviors such as fatigue. However, the signaling pathways involved are poorly defined. Circulating inflammatory mediator levels are increased in cholestasis, leading to speculation that they may be capable of activating circulating immune cells that subsequently could gain access to the brain. Indeed, we have identified that at day 10 after bile duct resection-induced cholestasis, there is activation of circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
84
1
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 51 publications
8
84
1
5
Order By: Relevance
“…The etiology of autonomic dysfunction in PBC is unclear; there may be both central and peripheral effects. In the central model brain injury, perhaps arising as a consequence of inflammatory processes occurring as a result of cholestasis inflammation (a model supported by animal modeling data for cholestasis 25 ), would affect autonomic regulating areas of the brain, leading to secondary peripheral autonomic effects. In the peripheral model vasomotor changes associated with liver disease and/or specific cardiac dysfunction associated with cardiac muscle abnormality in PBC 26,27 would give rise to processes mimicking central autonomic dysfunction peripherally.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of autonomic dysfunction in PBC is unclear; there may be both central and peripheral effects. In the central model brain injury, perhaps arising as a consequence of inflammatory processes occurring as a result of cholestasis inflammation (a model supported by animal modeling data for cholestasis 25 ), would affect autonomic regulating areas of the brain, leading to secondary peripheral autonomic effects. In the peripheral model vasomotor changes associated with liver disease and/or specific cardiac dysfunction associated with cardiac muscle abnormality in PBC 26,27 would give rise to processes mimicking central autonomic dysfunction peripherally.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed in animal models of cholestasis have suggested links between central nervous system changes resulting from cholestasis and fatigueassociated behavior patterns, 15,16 whereas magnetic resonance (MR) studies performed in human PBC have shown cholestasis-associated brain stem changes, the degree of which correlates strongly with fatigue severity. 17 A potential mechanism for the cholestasis-associated effects on both fatigue and sleep is suggested by the observation that, in cholestatic animal models, changes in brain inflammatory cytokine levels (possibly resulting from the recently demonstrated increase in central nervous system infiltrating cytokine releasing mononuclear seen in such animals 18 ) are strongly linked to fatigue-like behavior. Interleukin-6 is an inflammatory cytokine present at elevated levels in human liver with PBC 19,20 and is excessively released by both cultured biliary epithelial cells in response to hydrophobic bile acids of the type retained in the liver in cholestasis 21 and spontaneously by PBMC from patients with PBC.…”
Section: Discussionmentioning
confidence: 99%
“…However, etanercept indirectly reduces CNS inflammation by decreasing peripheral inflammation and preventing cross-talk (Kerfoot et al, 2006). This principal was evident in a 12 week treatment trial in psoriasis patients, where improved depressive symptoms were observed following subcutaneous etanercept injections (Tyring et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This association is likely related to extensive cross-talk occurring between immune cells within the central nervous system (CNS), such as microglia, and peripheral TNF-aproducing monocytes (Kerfoot et al, 2006). Peripheral lipopolysaccharide (LPS) inflammation activates Toll-like receptor 4 present on circumventricular organs and choroid plexus, resulting in NFkB activation and subsequent production of TNF-a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation